As TVs universitárias no contexto das indústrias culturais e midiáticas : o desafio conceitual e a busca de um modelo - Dias, Ana Paula Vieira de Souza (2016)
This work aims to show the importance of University TV from the point of view of the guarantee of rights, like the right to information, communication and education, and social point of view, as the body that can contribute to the democratization of communication and for the formation of active citizenship of individuals. Thus, considering that the University TV is a communication vehicle set up as part of an institution of education, the proposal is to analyze it located at the interface of these two areas: Communication and Education, understood from the perspective of Educommunication. This approach is the opposite of what here is called commercial media, that is only concerned with the profit generated by vehicles. Given this paradox and TV University as study object inserted in this context, comes up the following questioning: how the University TV can be on a commercial television feature counterpoint model of cultural and media industries? From this discussion, the general objective of the research is to understand the University TV in its entirety, clarifying their legal constitution, administrative, financial and logical that govern it in order to explain their way of working and seeking possible models for its constitution while publica television, committed to the values of Educommunication and promotion of citizenship. The work is in the line of research "Communication and Power", at the Master in Communication and Territorialities of the Federal University of Espírito Santo (Ufes), that proposes an analysis of a kind of media-communication device, noting that way it impacts the social, economic and political context in which it appears. To this end, the method used is the case study of six university TVs of federal universities, using literature, questionnaires answered by the managers of the selected TVs, sample analysis, data and documents collected. Adopt a critical perspective, from the theoretical framework of the Frankfurt School, the Political Economy of Communication and Educommunication. Finally, it is concluded that the lack of a model and a University TV project harms its consolidation. In this sense, we point out some indications of possible models for the establishment of University TVs so that they can expand their potential performance.